Was Kiobel Detrimental to Corporate Social Responsibility? Applying Lessons Learnt From American Exceptionalism - Thompson, Benjamin (Utrecht Journal of International and European Law, 2014)
The recent decision in the US Supreme Court Kiobel case applied the presumption against extraterritoriality towards the Alien Tort Statute, decreasing the potential scope of tort actions that can be made against corporations for severe human rights violations. In light of the growing influence of multinational corporations and the lack of any international law regime to regulate corporate wrongdoing, this decision might be seen as a blow against one of the few potential avenues for justice for those victims of corporate human rights violations. The Alien Tort Statute is not a jurisdictional statute that allows for claims under international law but is rather a uniquely American cause of action unconnected to international law. The question remains whether an extension of American law to provide remedies for severe corporate human rights abuses can be justified in the absence of any such remedies existent in international law. This article will attempt to answer this question applying criteria developed by leading scholars in response to American exceptionalism. It will argue that the Kiobel decision, rather than being detrimental to holding corporations accountable, actually addresses many of the negative aspects of extraterritorial litigation whilst preserving some possibility of remedy for victims of severe human rights violations by corporations.